Tracking a century of changes in microbial eukaryotic diversity in lakes driven by nutrient enrichment and climate warming. (22nd June 2017) - Capo, Eric; Debroas, Didier; Arnaud, Fabien; Perga, Marie‐Elodie; Chardon, Cécile; Domaizon, Isabelle
Summary: High‐throughput sequencing of sedimentary DNA (sed‐DNA) was utilized to reconstruct the temporal dynamics of microbial eukaryotic communities (MECs) at a centennial scale in two re‐oligotrophicated lakes that were exposed to different levels of phosphorus enrichment. The temporal changes within the MECs were expressed in terms of richness, composition and community structure to investigate their relationships with two key forcing factors (i.e., nutrient enrichment and climate warming). Various groups, including Apicomplexa, Cercozoa, Chrysophyceae, Ciliophora, Chlorophyceae and Dinophyceae, responded to phosphorus enrichment levels with either positive or negative impacts on their richness and relative abundance. For both lakes, statistical modelling demonstrated that phosphorus concentration ([P]) was a dominant contributor to MECs modifications before the 1980s; after the mid‐80s, the contribution of air temperature changes increased and potentially surpassed the contribution of [P]. Co‐occurrence network analysis revealed that some clusters of taxa (i.e., modules) composed mainly of Dinophyceae and unclassified Alveolata were strongly correlated to air temperature in both lakes. Overall, our data showed that sed‐DNA constitutes a precious archive of information on past biodiversity changes, allowing the study of the dynamics of numerous eukaryotic groups that were not traditionally considered in paleo‐reconstructions.